2011
DOI: 10.1021/ic102184n
|View full text |Cite
|
Sign up to set email alerts
|

Spin Structure of Surface-Supported Single-Molecule Magnets from Isomorphous Replacement and X-ray Magnetic Circular Dichroism

Abstract: Surface-supported arrays of Fe(4)-type Single-Molecule Magnets retain a memory effect and are of current interest in the frame of molecule-based information storage and spintronics. To reveal the spin structure of [Fe(4)(L)(2)(dpm)(6)] (1) on Au, an isomorphous compound [Fe(3)Cr(L)(2)(dpm)(6)] was synthesized and structurally and magnetically characterized (H(3)L is tripodal ligand 11-(acetylthio)-2,2-bis(hydroxymethyl)undecan-1-ol and Hdpm is dipivaloylmethane). The new complex contains a central Cr(3+) ion a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
42
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 15 publications
(28 reference statements)
10
42
0
Order By: Relevance
“…The maximum XMCD amplitude at 709.1 eV (ca. 40%) and the vanishing signal at 707.8 eV are considered fingerprints of the ferrimagnetic spin structure schematized in Figure a, where the central and peripheral iron ions provide opposing magnetic contributions . Our synchrotron investigation thus indicates that Au‐NPs are capped by intact SMMs.…”
Section: Resultsmentioning
confidence: 65%
“…The maximum XMCD amplitude at 709.1 eV (ca. 40%) and the vanishing signal at 707.8 eV are considered fingerprints of the ferrimagnetic spin structure schematized in Figure a, where the central and peripheral iron ions provide opposing magnetic contributions . Our synchrotron investigation thus indicates that Au‐NPs are capped by intact SMMs.…”
Section: Resultsmentioning
confidence: 65%
“…40,41 In an effort to synthesize heterometallic clusters with the same topology, in the past few years we have devised a procedure to replace the central iron(III) with a different tripositive metal ion M. The first synthetic method we described was based on a one-pot reaction and resulted in a solid solution of Fe 3 M and Fe 4 . 42,43 Much better suited for detailed spectroscopic studies are samples prepared through a three-step synthetic approach, which reduces the amount of Fe 4 to below the detection limit. 44 Of particular interest among these new heterometallic systems are Fe 3 Cr complexes characterized by an S = 6 ground state and an axial zero field splitting (zfs) parameter D ≅ -0.18 cm -1 .…”
Section: Introductionmentioning
confidence: 99%
“…The XMCD measured at the Fe and Cr L 2,3 edges on Fe 3 Cr tripod clusters, with a central Cr atom, deposited on Au showed that the antiparallel alignment between Fe and Cr spins is preserved on surfaces. 36 Cr 7 Ni ring spin clusters assembled on a Au substrate have also been investigated using XMCD technique as a function of temperature and field, demonstrating that the relative orientation between the Cr and the Ni magnetic moments changes from antiparallel to parallel with increasing temperature. 37 In addition, SMM behavior has also been proven in the endohedral system DySc 2 N@C 80 with complementary XMCD and SQUID measurements.…”
Section: Introductionmentioning
confidence: 99%